2011
DOI: 10.1007/s00572-011-0418-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Glomus irregulare, arbuscular mycorrhizal spore-associated bacteria, and plant pathogens under in vitro conditions

Abstract: Arbuscular mycorrhizal (AM) fungi interact with bacteria (AM fungi-associated bacteria, AMB) in the mycorrhizosphere. We previously identified a set of AMB that enhance AM fungal colonization, plant growth, and inhibit pathogens. Here, we used transformed carrot root cultures in a two-compartment plate system for further in vitro studies on interactions taking place among Glomus irregulare (syn.Glomus intraradices), AMB, and plant pathogens. We found that exudates of G. irregulare stimulated growth of all ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…While non-mycorrhizal fungi might have colonised plant roots and contributed to the transfer of signalling compounds, this is unlikely because AM fungi often antagonise soil pathogenic fungi (e.g. Bharadwaj et al 2012;Campos-Soriano et al 2012;Jung et al 2012) and the bean roots were confirmed to contain abundant arbuscules, which are specific to AM fungi. Moreover, bridges between plants formed by AM fungi can be established both by hyphal growth from one plant to another and by anastomosis where two hyphae of the same isolate fuse together and exchange nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…While non-mycorrhizal fungi might have colonised plant roots and contributed to the transfer of signalling compounds, this is unlikely because AM fungi often antagonise soil pathogenic fungi (e.g. Bharadwaj et al 2012;Campos-Soriano et al 2012;Jung et al 2012) and the bean roots were confirmed to contain abundant arbuscules, which are specific to AM fungi. Moreover, bridges between plants formed by AM fungi can be established both by hyphal growth from one plant to another and by anastomosis where two hyphae of the same isolate fuse together and exchange nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the microbiome attached to the hyphae was not associated with hyphal biomass but with hyphal exudates and suggests that different AMF may release different exudates. The composition of AMF hyphal exudates mainly consists of sugars, carboxylates and amino acids (Bharadwaj et al, 2012;Zhang et al, 2016), but how this differs from plant root exudates and between AMF species needs to be studied. Understanding the interaction between specific hyphal exudates and recruitment of PSB will be critical to allow us to manipulate the system effectively (Zhang et al, 2016).…”
Section: The Influences Of Plant Species and Phytate On The Compositimentioning
confidence: 99%
“…R12, the selenium level in the grains was improved compared to inoculating with either of the bacteria alone [45]. Besides, mycorrhizae also excrete H + and low-molecular weight organic chelating compounds, such as citric acid, oxalic acid, and siderophores, to solubilize Fe in soil [151]. Recently, mycorrhizal inoculation in wheat roots was reported to have increased the uptake of P, Fe, and Zn by the plant, along with greater root length and density [44].…”
Section: Endophytes As the Emerging Participant Of Microbe-mediated Bmentioning
confidence: 99%